El gozo del Paraíso en dísticos elegíacos: notas sobre algunos milagros marianos de Nigel de Canterbury - Disalvo, Santiago (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2017)
At the end of the 12th and during the 13th century, Marian miracle narrative moved from Latin prose to Romance verse, with authors such as Adgar, Gautier de Coinci, Gonzalo de Berceo and Alfonso X. Now, is there any evidence of poetic elaboration of miracles in Latin verse, as a moment of transition between Latin prose and Romance poetry? The answer is affirmative, and this is the case with the Miracula Sancte Dei Genitricis Virginis Marie, Versifice of Nigel of Canterbury. It is possible to consider, therefore, how narratives of wide usage, compiled mostly in brief stories in prose, become an elaborate collections in verse: miracles in elegiac couplets. In the abundance of tópoi that the author's clerical erudition employs, some particularly interesting images are introduced in order to examine the evolution of the description of Paradise in Marian literature